IMPACT OF SHADOW BANKING ACTIVITIES AS NON BANK INTERMEDIATION TOWARD REGULATORY DEVELOPMENTS IN FUNCTION CONTROL OF FINANCIAL SERVICES SECTOR IN INDONESIA - Lastuti Abubakar; C. Sukmadilaga; Tri Handayani (Fakultas Hukum, Universitas Diponegoro, 2016)
Based on the Global Shadow Banking Monitory Report 2015 issued by the Financial Stability Board, global shadow banking activities manage 80% of global GDP and 90% of the global financial system assets. Hence, this study aimed to examine the regulation and supervision of shadow banking activities in Indonesia. The method used is normative juridical with descriptive analytical research specifications. Based on the research results as follows : regulation of shadow banking in Indonesia's financial services sector covers all financial institutions outside the banking sector or Non-Bank Financial Institutions that the regulations are scattered in various rules. Indonesia has developed an integrated surveillance system for the entire financial services sector, include NBFIs. Development of shadow banking regulation will be based on the strengthening of reporting, monitoring, supervision and regulation. Keywords : regulatory developments, shadow banking, and supervision